Potensi Kombucha Sebagai Minuman Probiotik Dan Sumber Antioksidan - Putri, Aisya Kamila; Sabrina, Sabrina (Peneliti.net, 2024)
Excessive free radicals can lead to detrimental oxidative stress. Low antioxidant activity can trigger health issues like metabolic disorders and cell degeneration. Kombucha is the product of tea and sugar fermentation by a symbiosis of bacteria and yeast, offering benefits such as antioxidants, antibacterial properties, and immune support. The goal of this study is to explore the potential of kombucha as a probiotic beverage rich in antioxidant properties. A literature review of 8 research articles on antioxidant activity in kombucha was conducted. Articles were obtained through Google Scholar and the Garuda portal using the keyword